Studi Pendahuluan Sintesis Nano-partikel Cobalt-ferit Hasil Ko-presipitasi: Rafika Rahmawati, Suharyana, Budi Purnama - Rafika Rahmawati, Rafika Rahmawati; Suharyana, Suharyana; Budi Purnama, Budi Purnama (Jurnal Fisika dan Aplikasinya, 2025)
Preliminary study on the synthesis of ferromagnetic cobalt ferrite nanoparticles by co-precipitation method followed by annealing process has been done. Annealing was performed at atmospheric condition. The TG-DTA characterization results showed that the crystal growth process occured at above 5000 C. The XRD spectra of the sample showed that the crystal structure of CoFe2O4 was confirmed with the main diffraction peak at 2O = 35.70 corresponding to (hkl) indeks of 311. Finally, analysis of vibrating sample magnetometer indicated that cobalt ferrite sample had coercive field of H = 313 Oe.